A New Silicon Dioxide-Coated MALDI-ToF Sample Plate for Peptide Analysis. (30th June 2020) - Huang, He; Sun, Lei; He, Haiyang; Xia, Tianbao
Abstract : In this report, we describe the development and testing of a new coated plate which improves the sensitivity and accuracy in matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF-MS). The coated plate was covered with a thin layer of hydrophobic silicon dioxide, which enabled sample enrichment due to the water repellent nature of the silicon dioxide surface. Sensitivity and required laser strengths were tested using peptide standards, with the results that these coated plates required lower laser power and showed increased sensitivity than that of common plates. Accuracy was tested using bacteria, saliva, and serum samples. The coated plates showed significantly increased degrees of accuracy through their capacity to reduce mass shift. The importance and necessity of accuracy analysis in the assessment of new sample plates, which is rarely described in other papers, is also discussed.